Computational structural biology and modes of interaction between human annexin A6 with influenza A virus protein M2: a possible mechanism for reducing viral infection. (2018) - Ray, Sujay; Banerjee, Arundhati
Influenza-A virus is a prime lethal causative factor for influenza. The M2 protein of influenza A virus plays an important responsibility in the cycle of viral replication. The human Annexin A6 protein targets and stops the viral budding for influenza A virus. Here, molecular level interactions between Annexin A6 and influenza A virus M2 protein were examined. Executing the techniques for molecular modelling, the 3D structures of the two proteins were built via energy optimisations. Interactions between the two proteins were analysed by molecular docking studies. Both Annexin A6 and M2 protein interacted strongly with a pivotal role of Asp and Lys residues, respectively. A conformational shift from helices and sheets to coils was observed in the M2 protein after its interaction with Annexin A6. This probe therefore helped to understand the molecular mechanism of the two proteins and the negative modulation of Annexin A6 on the M2 protein from influenza A virus.